KONTRUKSI GENDER DAN PERLAWANAN TOKOH PEREMPUAN DALAM NOVEL TERUSIR KARYA HAMKA - Pita Pita; Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to examine the construction of gender and forms of resistance by female characters in the novel Terusir by Hamka using a feminist approach. The research addresses how gender construction is portrayed and how female characters resist gender injustice within a patriarchal cultural context. The method used is qualitative with a library research design. The primary data source is the novel Terusir, while secondary data includes feminist theories, particularly Kate Millett‟s theory, along with relevant literature. Data collection was carried out through literature study by reading, noting, classifying, and analyzing key excerpts. The results show that the character Mariah experiences various forms of gender construction that place her in a subordinate position, such as submission to male authority and social stigma. However, Mariah is portrayed as a figure capable of resistance through perseverance, independence, and rejection of patriarchal norms. The novel serves as a form of social criticism against gender inequality institutionalized within patriarchal culture.